Desenvolvimento, caracterização físico-química e atividade anti-inflamatória in vivo de complexos de inclusão do óleo-resina de Copaifera multijuga Hayne em ciclodextrinas - Pinheiro, Jonas Gabriel de Oliveira (2017)
Copaifera multijuga Hayne trees grows abundantly in Amazon region, presenting wide visibility for its oleoresin, which shows anti-inflammatory activity. The inclusion complex (IC) formation with cyclodextrin (CD) has been applied as alternative to solve some limitations that oils have in common, principally the poor aqueous solubility. Thus, this work aimed the ICs development of Copaifera multijuga oleoresin (CMO) with β-cyclodextrin (βCD) and with hydroxypropyl-β-cyclodextrin (HPβCD) and evaluating of its anti-inflammatory activities. Initially, it were realized computational theoretical studies, in which were calculated the interaction energies between βCD e o β-caryophyllene (βCP), most abundant compound in CMO. Next, it were prepared βCD and HPβCD IC’s by physical mixture, kneading method (KND) and slurry method (SL). ICs physical-chemical characterization was realized by Fourier transform infrared absorption region spectroscopy (FTIR), scanning electronic microscopy (SEM), powder X-ray diffraction (XRD), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). Finally, βCD and HPβCD IC’s were compared to pure CMO, in relation to its anti-inflammatory activity. Computational theoretical studies showed energetic values of -20.8 kcal∙mol-1 and -17.0 kcal∙mol-1 of complexation with βCP minor and lager face, respectively, entering through the βCD larger cavity side. In FTIR, it was possible observing that occurred interaction between βCD and CMO by KND and SL, and between HPβCD and CMO by SL. In SEM, in XRD and in TGA, it was possible conclude that there was interaction between βCD and CMO by KND and SL. In DSC case, it was observed that occurred interaction between βCD and CMO and between HPβCD and CMO by KND and SL. CMO and βCD and HPβCD ICs showed evident anti-inflammatory activity by paw edema, nitrite concentration and myeloperoxidase activity decreasing, evidencing that ICs of CMO with βCD and HPβCD, which keeping the CMO anti-inflammatory activity.